1993
DOI: 10.1172/jci116730
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and genetic analyses of inbred mouse strains with a type I iodothyronine 5' deiodinase deficiency.

Abstract: Inbred mouse strains differ in their capacity to deiodinate iododioxin and iodothyronines, with strains segregating into high or low activity groups. Metabolism of iododioxin occurs via the type I iodothyronine 5'deiodinase (51DI), one of two enzymes that metabolize thyroxine (T4) to 3,5,3'-triiodothyronine (T3). Recombinant inbred strains derived from crosses between high and low activity strains exhibit segregation characteristic of a single allele difference. Hepatic and renal 5DI mRNA in a high (C57BL/6J) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 55 publications
6
29
1
2
Order By: Relevance
“…Besides the reduced hepatic and renal D1 activity, the most notable features of the C3H mouse are that, when compared with the C57 mouse, the circulating levels of T 4 and rT 3 are elevated, while those of TSH and T 3 are unchanged. It would therefore be anticipated that in C3H mice the higher serum free T 4 concentration would cause a decrease in D2 activity, which was confirmed by twofold lower D2 activity in pituitary and brain (Berry et al 1993). Here, we demonstrated that the D2 mRNA levels are not different between C3H and C57 mice, providing additional evidence that the reduced D2 activity in C3H mice results from an increased rate of substrate-induced enzyme inactivation.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Besides the reduced hepatic and renal D1 activity, the most notable features of the C3H mouse are that, when compared with the C57 mouse, the circulating levels of T 4 and rT 3 are elevated, while those of TSH and T 3 are unchanged. It would therefore be anticipated that in C3H mice the higher serum free T 4 concentration would cause a decrease in D2 activity, which was confirmed by twofold lower D2 activity in pituitary and brain (Berry et al 1993). Here, we demonstrated that the D2 mRNA levels are not different between C3H and C57 mice, providing additional evidence that the reduced D2 activity in C3H mice results from an increased rate of substrate-induced enzyme inactivation.…”
Section: Discussionsupporting
confidence: 68%
“…However, the expression of D2, another T 4 -activating enzyme, has not been entirely assessed in D1-deficient mice. Comparative analysis of D2 activity levels between C3H and C57 mice demonstrated that pituitary and brain D2 activity in C3H mice was about 50% lower than that in C57 animals (Berry et al 1993), which is attributed to the twofold increase in serum T 4 concentration. The D2 mRNA expression has not been evaluated in the C3H mouse.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Whether this means that these mutations are not compatible with life, that they have little or no consequences, or that they result in unexpected phenotypes is unclear. Based on the phenotypes of mice with targeted deletions of D1, D2, or D3, the most severe effects would be expected of mutations in D3 (43)(44)(45). In the last few years, several polymorphisms in deiodinases have been described (17,46,47) (Fig.…”
Section: Polymorphisms In the Iodothyronine Deiodinasesmentioning
confidence: 99%
“…В активном центре трех дейодиназ присутствует редкая аминокислота -селеноцистеин [6]. В селено-протеинах кодон UGA кодирует не терминацию трансляции белка, а инсерцию селеноцистеина.…”
unclassified